The Role of Fiscal Transfers in Smoothing Regional Shocks : Evidence from Existing Federations - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2016)
We assess the extent to which fiscal transfers smooth regional shocks in three large federations: the U.S., Canada, and Australia. We find that fiscal transfers offset 4-11 percent of idiosyncratic shocks (risk-sharing) and 13-24 percent of permanent shocks (redistribution). This fiscal insurance largely operates through automatic stabilizers embedded in a central budget primarily through federal taxes and transfers to individuals, rather than transfers from the central government to state budgets. These results have implications for the design of fiscal risk-sharing mechanisms in the euro area.